Population-based geographic access to endocrinologists in the United States, 2012. Issue 1 (June 2015) - Lu, Hua; Holt, James; Cheng, Yiling; Zhang, Xingyou; Onufrak, Stephen; Croft, Janet
Abstract Background Increases in population and life expectancy of Americans may result in shortages of endocrinologists by 2020. This study aims to assess variations in geographic accessibility to endocrinologists in the US, by age group at state and county levels, and by urban/rural status, and distance. Methods We used the 2012 National Provider Identifier Registry to obtain office locations of all adult and pediatric endocrinologists in the US. The population with geographic access to an endocrinologist within a series of 6 distance radii, centered on endocrinologist practice locations, was estimated using the US Census 2010 block-level population. We assumed that persons living within the same circular buffer zone of an endocrinologist location have the same geographic accessibility to that endocrinologist. The geographic accessibility (the percentage of the population with geographic access to at least one endocrinologist) and the population-to-endocrinologist ratio for each geographic area were estimated. Results By using 20 miles as the distance radius, geographic accessibility to at least one pediatric/adult endocrinologist for age groups 0–17, 18–64, and ≥65 years was 64.1 %, 85.4 %, and 82.1 %. The overall population-to-endocrinologist ratio within 20 miles was 39, 492:1 for children, 29, 887:1 for adults aged 18–64 years, and 6, 194:1 for adults aged ≥65 years. These ratios varied considerably by state, county, urban/rural status, and distance. Conclusions This study demonstrates that there are geographic variations of accessibility to endocrinologists in the US. The areas with poorer geographic accessibility warrant further study of the effect of these variations on disease prevention, detection, and management of endocrine diseases in the US population. Our findings of geographic access to endocrinologists also may provide valuable information for medical education and health resources allocation.